Method for preparing doped carbon-loaded single-site metal catalyst by using nitrogen-containing waste plastic and application of doped carbon-loaded single-site metal catalyst
The nitrogen-containing waste plastic after hydrothermal pretreatment and metal foam were prepared with high temperature reaction under an inert atmosphere. The unit-point metal catalyst with doped carbon-loaded was solved, and the problem of landfill and pyrolytic pollution of nitrogen-containing waste plastic was achieved, achieving the effect of rapid and efficient degradation of plastics.
Patent Information
- Application Number
- CN202411706589.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-11-26
AI Technical Summary
Landfill of nitrogen-containing waste plastics leads to environmental pollution, heat releases toxic gases, chemical degradation products are difficult to separate, and the existing single-atom catalyst preparation methods are poor in economicality and the preparation process is complicated.
The nitrogen-containing waste plastic after hydrothermal treatment reacts with metal foam at high temperature under an inert atmosphere to prepare a unit point metal catalyst with doped carbon-supported, and catalytic degradation is carried out with microwave assistance.
The preparation process is simplified, energy consumption and cost are reduced, the added value of the catalyst is increased, and the ability to quickly and efficiently degrade polyester, polycarbonate, epoxy resin and polyurethane resin plastics.
Smart Images

Figure CN119588394A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a carbon-doped loaded single-site metal catalyst by utilizing nitrogen-containing waste plastics and the application of microwave-assisted rapid degradation of polyester, polycarbonate and polyurethane resin plastics, belonging to the field of plastic solid waste recycling and resource utilization. Background Art
[0002] Plastic recycling and chemical upgrading have been the focus of renewable resource research in recent years. Nitrogen-containing waste plastics account for a large proportion of the world's total waste plastics. The nitrogen-containing waste plastics used in the present invention include melamine resin, urea-formaldehyde resin, melamine urea-formaldehyde resin and polyurethane.
[0003] Melamine resin (MFR), also known as melamine formaldehyde resin, is a cross-linked polymer obtained by condensation of melamine and formaldehyde. It is a thermosetting plastic with a triazine ring structure connected by repeated methylene groups and is widely used in tableware, toys and imitation glaze crafts. Urea-formaldehyde resin (UF), also known as urea-formaldehyde resin, is a polymer with -NH2-CO- structural units formed by condensation of urea and formaldehyde under the action of a catalyst. Initial urea-formaldehyde resins are mainly used as adhesives. Late urea-formaldehyde resins are cross-linked thermosetting plastics, mainly used in electrical instruments and sound insulation, thermal insulation materials, etc. Melamine urea-formaldehyde resins (MUF) are a type of plastic formed by condensation of melamine, urea and formaldehyde. They are mainly used in adhesives and melamine urea-formaldehyde foams. Polyurethane (PU), also known as polyurethane, is a polymer material with carbamate segments (-NHCOO-) formed by the polycondensation of polyols and polyisocyanates. It is mainly used as soft / hard foam plastics, elastomers, fiber plastics, adhesives, etc. in textiles, construction, shoemaking and medical industries. These nitrogen-containing waste plastics will slowly decompose into formaldehyde, organic ammonia and other toxic and harmful substances that pollute the environment when landfilled ( Molecules 2020, 25 (16), 3629). The incineration process also produces a large amount of toxic gases. In addition, chemical recycling can only produce a mixture, which is difficult to separate and purify and consumes a lot of energy ( Green Chemistry 2021, 23 (19), 7816-7824; Green Chemistry , 2024, 26(3), 1132).
[0004] Metal single-site catalysts are supported catalysts with isolated metal single-atom sites as active centers, which are composed of metal single-atom sites and carriers. The utilization rate of metal atoms reaches 100%. It has excellent catalytic activity and selectivity and can be used in the fields of energy, petrochemicals and environmental protection. At present, the main methods for synthesizing metal single atoms are wet chemical method (CN202311718095; CN202410431144), defect design strategy ( ACS Catalysis 2018, 8,4044-4048) and electrochemical deposition method ( Nature Communications 2016, 7, 10667) and high temperature pyrolysis (CN202410186099; Chemical Reviwes 2020, 120, 21, 11900-11955), etc. Among them, the wet chemical method requires precise control of the ratio of metal salts, carrier precursors and solvents, and the metal loading per unit point is low. The electrochemical deposition method requires the carrier to have good conductivity, and the reduction process easily forms metal particle agglomerates. The defect design strategy requires single atoms to be specifically adsorbed on metal oxide carriers with abundant oxygen vacancies. Li Yadong used high-temperature pyrolysis to convert the zeolite imidazole framework into a metal single-site catalyst. This process requires precise control of the metal ratio and the pyrolysis rate of the zeolite imidazole framework. Subsequently, Li Yadong and Wu Yuen used pyrolysis of small organic molecules or zeolite imidazole frameworks to obtain ammonia molecules coordinated with bulk metals to form M(NH3) x , which is then captured by defects in the nitrogen-rich carbon support to yield a metal single-site catalyst ( Nature Catalysis 2018,1, 781-786). This process requires precise control of the pyrolysis rate of small organic molecules, the generation rate of nitrogen-rich carbon carriers, and the relative distance between ammonia molecule precursors and bulk metals, and consumes small organic molecules, which is not economical. In summary, these methods usually require special equipment or complex carrier preparation and pre-modification, which is not economical and seriously limits the large-scale preparation and practical application of single-atom catalysts.
[0005] Polyester resin plastics are linear polymers composed of repeating units connected by ester bonds. Due to their excellent properties, such as high strength, high heat resistance, acid and alkali resistance, they are widely used in packaging, textile, automotive and other industries. Polyurethane is a polymer material with a carbamate segment (-NHCOO-) formed by the polycondensation of polyols and polyisocyanates. It is mainly used in textiles, construction, shoemaking and medical industries. Polycarbonate is a carbonate-based polymer. Due to its excellent optical properties, it is widely used in the glass assembly industry, automobile industry, electronics and electrical industry. Epoxy resin is an organic polymer compound containing two or more epoxy groups. It can undergo cross-linking reactions with curing agents such as organic amines, polyamides, and acid anhydrides to form an insoluble, infusible thermosetting polymer with a network structure. It is widely used in mechanical electronics, aerospace, automotive military and other fields. However, the large-scale use and disposal of polyester, polycarbonate, epoxy resin, and polyurethane resin plastics seriously pollute the environment and are also a waste of resources. Chemical recycling of monomer molecules or polyols is a green recycling route ( Green Chemical Engineering , 2024, 5(2), 257-265; Polymer , 2017, 117(19), 183-197; Green Chemistry , 2024, 26, 1132), however, the above process requires the use of inorganic or organic acid (or base) catalysts, and the reaction time is long and the energy consumption is high.
[0006] Therefore, it is urgent to develop a simple and easy-to-control upgrading method for nitrogen-containing waste plastics, which reduces the use of organic solvents, does not require complex pretreatment and chemical synthesis, and has high added value. At the same time, it is urgent to develop a method for rapid degradation and catalytic degradation of polyester, polycarbonate, epoxy resin and polyurethane resin plastics. Summary of the invention
[0007] In view of the shortcomings of waste nitrogen-containing plastics in landfill treatment, such as environmental pollution, toxic gas release during pyrolysis and difficulty in separating chemical degradation products, the present invention has developed a simple and efficient method for preparing doped carbon-loaded metal single-site catalysts using nitrogen-containing waste plastics, and applied it to the microwave-assisted rapid catalytic degradation of polyester, polycarbonate, epoxy resin and polyurethane resin plastics.
[0008] In order to achieve the above object, the present invention adopts the following technical solutions: A method for preparing a doped carbon-supported single-site metal catalyst using nitrogen-containing waste plastics comprises the following steps: The nitrogen-containing waste plastics are crushed and dispersed into water, and then hydrothermally pretreated at 120-280°C in a sealed container; The solid product was obtained after evaporation of the solvent and drying; (3) The solid product is evenly spread on a heat-resistant substrate, and metal foam is placed on it. The reaction is carried out at 700~1200℃ under an inert atmosphere to obtain a doped carbon-supported single-site metal catalyst.
[0009] In the above step (1), the nitrogen-containing waste plastic is dispersed in water, and the volume ratio of the nitrogen-containing waste plastic to water is R 0.2~0.01 g∙mL -1 The nitrogen-containing waste plastic is selected from melamine resin, melamine urea-formaldehyde resin, urea-formaldehyde resin, and polyurethane.
[0010] In the above step (1), the pretreatment is carried out at 120-280°C for 2-4 h.
[0011] In the above step (2), the evaporation of the solvent is preferably performed by evaporating the pretreated mixture at 50-80°C under assisted air bubbling to promote water evaporation and reduce material loss.
[0012] In the above step (3), the metal foam is selected from foamed iron, foamed nickel, foamed cobalt, foamed copper, foamed silver, foamed nickel iron or foamed nickel cobalt. The mass ratio of the metal foam to the plastic solid is W It is 0.01~0.2.
[0013] In the above step (3), the metal loading mass fraction of the obtained carbon-doped supported unit-site metal catalyst is 10-20%.
[0014] In the above step (3), the inert atmosphere is an inert gas such as nitrogen or argon. -1 The temperature is raised to 700-1200°C at a rate of 100°C and kept at this temperature for 5-30 min to obtain a carbon-doped single-site metal catalyst.
[0015] The doped carbon-supported single-site metal catalyst prepared by the above method can catalyze the degradation of polyester, polycarbonate (PC), epoxy resin (EP) and polyurethane (PU) waste plastics.
[0016] Specifically, the method for catalytic degradation of waste plastics is: adding a catalytic amount of a doped carbon-loaded single-site metal catalyst to a waste plastic dispersion, and after ultrasonic dispersion, forming a solid-liquid dispersion slurry, and catalytic degradation is carried out under the assistance of microwaves.
[0017] The solvent in the waste plastic dispersion is selected from water, methanol, ethanol, acetic acid, ethylene glycol, and diethylene glycol, and the ratio of the mass (g) of the waste plastic to the volume (mL) of the solvent is R , R = m (Waste Plastic) / V (Solvent), R0.01~0.5 g∙mL -1 .
[0018] The microwave power of the microwave-assisted catalytic degradation is 500-2000 W, the reaction temperature is 100-280° C., the reaction time is 0.5-20 min, and the reaction pressure is 0.1-2 MPa.
[0019] The polyester plastics are polyethylene terephthalate (PET), polybutylene terephthalate (PBT), and polycaprolactone (PCL).
[0020] Advantages and beneficial effects of the present invention: (1) In view of the shortcomings of waste nitrogen-containing waste plastics that pollute the environment when landfilled, release toxic gases during pyrolysis, and are difficult to separate chemical degradation products, the present invention has developed a method for preparing a carbon-doped metal single-site catalyst using waste nitrogen-containing plastics; the nitrogen-containing small molecules generated by the pyrolysis of waste nitrogen-containing plastics are captured by foam metal to form a carbon-doped metal single-site catalyst; the waste nitrogen-containing waste plastics have a high thermal decomposition temperature and a relatively slow rate of releasing nitrogen-containing small molecules, and have a strong interaction with the foam metal, so that the preparation conditions and parameters of the synthesized single-site metal catalyst are simple and controllable; the pretreatment and preparation process are simple, and no synthetic carrier and precursor are required; using waste nitrogen-containing plastics as raw materials, it is environmentally friendly and low-cost, and a high-value-added carbon-doped metal single-site catalyst can be obtained. (2) In view of the problem of slow degradation rate of waste polyester, polycarbonate, epoxy resin and polyurethane resin plastics, the present invention has developed a rapid microwave-assisted catalytic degradation method, and the prepared carbon-doped metal single-site catalyst achieves rapid and efficient degradation of waste polyester, polycarbonate, epoxy resin and polyurethane resin plastics. (3) Using carbon-doped metal single-site catalysts to produce in-situ thermal effects under microwave irradiation, the rapid and efficient degradation of discarded polyester, polycarbonate, epoxy resin and polyurethane resin plastics can be achieved at lower reaction temperatures and pressures; continuous degradation can be achieved using a microwave high-pressure continuous flow reactor. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 Schematic diagram of pyrolysis of hydrothermal treatment products of waste plastics covered with foam metal; Figure 2 High-angle annular dark-field scanning transmission electron microscopy image of Example 1; Figure 3 High-angle annular dark-field scanning transmission electron microscopy image of Example 4; Figure 4 Transmission electron microscopy image of Example 11; Figure 5 Transmission electron microscopy image of Example 12; Figure 6High-angle annular dark-field scanning transmission electron microscopy image of Example 13; Figure 7 Infrared comparison of the degradation product terephthalic acid in Example 15 and the commercially available product. DETAILED DESCRIPTION
[0022] Below in conjunction with specific embodiment of the present invention, technical scheme of the present invention is clearly and completely described, it is obvious that described embodiment is only a part of embodiment of the present invention, rather than whole embodiment. The reagent, method and equipment adopted in the present invention are conventional reagents, methods and equipment in the art. Based on the embodiment in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work premise belong to the scope of protection of the present invention. Example 1
[0023] Disperse 5.0 g of melamine resin in 500 mL of water. R = 0.01, the dispersion was transferred to a sealed container and pretreated at 200 °C for 3 h. The resulting mixture was evaporated at 60 °C. During the evaporation process, auxiliary air bubbling was used to promote water evaporation and reduce material loss. Subsequently, the solid product was dried in a vacuum drying oven at 90 °C for 8 h. Figure 1 As shown, 0.2 g of the solid product was evenly spread in a porcelain boat crucible, and 0.02 g of nickel foam was placed on it. W = 0.1. In a tube furnace, under nitrogen atmosphere (flow rate 50 mL∙min -1 ), at 2℃ min -1 The temperature was raised to 800°C at a rate of 1.000 °C. After calcination at this temperature and atmosphere for 1 h, 0.08 g of nitrogen-oxygen doped carbon-supported single-site Ni catalyst was obtained, with a loading of 11.3%. High-angle annular dark field scanning transmission electron microscopy images show that Ni is dispersed on nitrogen-oxygen doped carbon in the form of isolated metal single atom sites ( Figure 2 ).
[0024] Comparison examples The process of this comparative example is the same as that of Example 1, except that no foamed nickel is placed during the roasting process, and only 0.07 g of nitrogen-oxygen-doped carbon is obtained by roasting. Example 2
[0025] Disperse 1.0 g of melamine resin in 20 mL of water. R = 0.05, transfer the dispersion into a sealed container and heat at 280 ℃ for 2.5 hours. The obtained mixture was evaporated at 70℃. During the evaporation process, auxiliary air bubbling was used to promote water evaporation and reduce material loss. Subsequently, the solid product was dried in a vacuum drying oven at 90℃ for 8 h. 0.5 g of the solid product was evenly spread in a porcelain boat crucible, and 0.075 g of cobalt foam was placed on it. W = 0.15. In a tube furnace, under nitrogen atmosphere (flow rate 100 mL∙min -1 ), at 8℃ min -1 The temperature was raised to 900 °C at a rate of 1.5 °C. At this temperature and atmosphere, after constant temperature calcination for 0.5 h, 0.21 g of nitrogen-oxygen-doped carbon-supported single-site Co catalyst was obtained with a loading of 15.1%. Example 3
[0026] Disperse 3.0 g of polyurethane in 30 mL of water. R = 0.1, transfer the dispersion into a sealed container and heat at 120 ℃ for 4 hours. The obtained mixture was evaporated at 50℃. During the evaporation process, auxiliary air bubbling was used to promote water evaporation and reduce material loss. Subsequently, the solid product was dried in a vacuum drying oven at 120℃ for 2 h. 0.3 g of the solid product was evenly spread in a porcelain boat crucible, and 0.015 g of zinc foam was placed on it. W = 0.05. In a tube furnace, under argon atmosphere (flow rate 150 mL∙min -1 ), at 2℃ min -1 The temperature was raised to 700 °C at a rate of 1.5 ℃. At this temperature and atmosphere, after constant temperature calcination for 6 h, 0.11 g of nitrogen-oxygen-doped carbon-supported single-site Zn catalyst was obtained with a loading of 10.1%. Example 4
[0027] Disperse 4.0 g of polyurethane in 200 mL of water. R = 0.02, transfer the dispersion into a sealed container and heat at 150 ℃ for 3 hours. The obtained mixture was evaporated at 60℃. During the evaporation process, auxiliary air bubbling was used to promote water evaporation and reduce material loss. Subsequently, the solid product was dried in a vacuum drying oven at 100℃ for 4 h. 0.4 g of the solid product was evenly spread in a porcelain boat crucible, and 0.004 g of foamed copper was placed on it. W = 0.01. In a tube furnace, under nitrogen atmosphere (flow rate 50 mL∙min -1 ), at 5℃ min -1 The temperature was raised to 800 °C at a rate of 1.5 ℃. At this temperature and atmosphere, after constant temperature calcination for 5 h, 0.16 g of nitrogen-oxygen-doped carbon-supported unit-site Cu catalyst was obtained with a loading of 12.8%. Example 5
[0028] Disperse 0.8 g of urea-formaldehyde resin in 50 mL of water. R = 0.016, transfer the dispersion into a sealed container and heat at 180 ℃ for 3 hours. The obtained mixture was evaporated at 70℃. During the evaporation process, auxiliary air bubbling was used to promote water evaporation and reduce material loss. Subsequently, the solid product was dried in a vacuum drying oven at 110℃ for 3 h. 0.2 g of the solid product was evenly spread in a porcelain boat crucible, and 0.04 g of nickel foam was placed on it. W = 0.2. In a tube furnace, under nitrogen atmosphere (flow rate 10 mL∙min -1 ), at 7℃ min -1 The temperature was raised to 900 °C at a rate of 1.5 ℃. At this temperature and atmosphere, after constant temperature calcination for 4 h, 0.06 g of nitrogen-oxygen-doped carbon-supported single-site Ni catalyst was obtained with a loading of 12.4%. Example 6
[0029] Disperse 2.4 g of urea-formaldehyde resin in 80 mL of water. R = 0.03, transfer the dispersion into a sealed container and heat at 210 ℃ for 3.5 hours. The obtained mixture was evaporated at 50℃. During the evaporation process, auxiliary air bubbling was used to promote water evaporation and reduce material loss. Subsequently, the solid product was dried in a vacuum drying oven at 110℃ for 12 h. 0.3 g of the solid product was evenly spread in a porcelain boat crucible, and 0.03 g of foamed iron was placed on it. W = 0.1. In a tube furnace, under argon atmosphere (flow rate 150 mL∙min -1 ), at 10℃ min -1 The temperature was raised to 1000°C at a rate of 1000°C. After constant temperature calcination for 2 h at this temperature and atmosphere, 0.09 g of nitrogen-oxygen doped carbon-supported single-site Fe catalyst was obtained, with a loading of 10.5%. High-angle annular dark field scanning transmission electron microscopy images show that Fe is dispersed on nitrogen-oxygen doped carbon in the form of isolated metal single atom sites ( Figure 3 ). Example 7
[0030] Disperse 1.0 g of melamine urea-formaldehyde resin in 100 mL of water. R= 0.01, transfer the dispersion to a sealed container and pretreat at 160°C for 3 hours. The resulting mixture is evaporated at 50°C. During the evaporation process, auxiliary air bubbling is used to promote water evaporation and reduce material loss. Subsequently, the solid product is dried in a vacuum drying oven at 110°C for 3 h. Take 0.4 g of the solid product and spread it evenly in a porcelain boat crucible, and place 0.06 g of foamed copper on it. W = 0.15. In a tube furnace, under argon atmosphere (flow rate 200 mL∙min -1 ), at 15℃ min -1 The temperature was raised to 1100°C at a rate of 1.000 ℃. At this temperature and atmosphere, after constant temperature calcination for 1 hour, 0.17 g of nitrogen-oxygen-doped carbon-supported unit-site Cu catalyst was obtained with a loading of 12.5%. Example 8
[0031] Disperse 1.6 g of melamine urea-formaldehyde resin in 20 mL of water. R = 0.08, transfer the dispersion into a sealed container and heat at 250 ℃ for 2 hours. The obtained mixture was evaporated at 60℃. During the evaporation process, auxiliary air bubbling was used to promote water evaporation and reduce material loss. Subsequently, the solid product was dried in a vacuum drying oven at 80℃ for 2 h. 0.5 g of the solid product was evenly spread in a porcelain boat crucible, and 0.02 g of foamed silver was placed on it. W = 0.04. In a tube furnace, under nitrogen atmosphere (flow rate 180 mL∙min -1 ), at 20℃ min -1 The temperature was raised to 1200°C at a rate of 1.5 ℃. At this temperature and atmosphere, after constant temperature calcination for 0.5 h, 0.16 g of nitrogen-oxygen-doped carbon-supported single-site Ag catalyst was obtained with a loading of 10.3%. Example 9
[0032] Disperse 1.0 g of melamine resin and 1.0 g of urea-formaldehyde resin in 10 mL of water. R = 0.2, transfer the dispersion into a sealed container and heat at 260 ℃ for 2 hours. The obtained mixture was evaporated at 70℃. During the evaporation process, auxiliary air bubbling was used to promote water evaporation and reduce material loss. Subsequently, the solid product was dried in a vacuum drying oven at 80℃ for 2 h. 0.3 g of the solid product was evenly spread in a porcelain boat crucible, and 0.03 g of foamed iron-nickel was placed on it. W = 0.1. In a tube furnace, under an argon atmosphere (flow rate 100 mL∙min -1 ), at 6℃ min -1The temperature was raised to 700 °C at a rate of 1.5 °C. At this temperature and atmosphere, after constant temperature calcination for 6 h, 0.15 g of nitrogen-oxygen-doped carbon-supported unit-site Fe and Ni catalysts were obtained, with loadings of 1.7% and 8.5%, respectively. Example 10
[0033] Disperse 1.4 g polyurethane and 1.4 g urea-formaldehyde resin in 20 mL water. R = 0.14, transfer the dispersion into a sealed container and heat at 230 ℃ for 2 hours. The obtained mixture was evaporated at 80℃. During the evaporation process, auxiliary air bubbling was used to promote water evaporation and reduce material loss. Subsequently, the solid product was dried in a vacuum drying oven at 60℃ for 2 h. 0.4 g of the solid product was evenly spread in a porcelain boat crucible, and 0.06 g of nickel-cobalt foam was placed on it. W = 0.15. In a tube furnace, under argon atmosphere (flow rate 160 mL∙min -1 ), at 7℃ min -1 The temperature was raised to 900 °C at a rate of 1.5 ℃. At this temperature and atmosphere, after constant temperature calcination for 3 h, 0.14 g of nitrogen-oxygen-doped carbon-supported unit-site Ni and Co catalysts were obtained, with loadings of 7.7% and 2.4%, respectively. Embodiment 11
[0034] Disperse 0.5 g of polyethylene terephthalate in 50 mL of water. R = 0.01, transfer the dispersion into a sealed container and heat at 200 ℃ for 3 hours. The obtained mixture was evaporated at 60℃. During the evaporation process, auxiliary air bubbling was used to promote water evaporation and reduce material loss. Subsequently, the solid product was dried in a vacuum drying oven at 90℃ for 8 h. 0.2 g of the solid product was evenly spread in a porcelain boat crucible, and 0.02 g of nickel foam was placed on it. W = 0.1. In a tube furnace, under nitrogen atmosphere (flow rate 50 mL∙min -1 ), at 2℃ min -1 The temperature was raised to 800°C at a rate of 100°C. After calcination at this temperature and atmosphere for 1 hour, 0.06 g of Ni nanoparticles supported by oxygen-doped carbon were obtained, with a loading of 10.5%. Transmission electron microscopy images showed that Ni was dispersed on nitrogen-oxygen doped carbon in the form of metal nanoparticles ( Figure 4 ). Example 12
[0035] Disperse 5.0 g of melamine resin in 500 mL of water. R = 0.01, transfer the dispersion into a sealed container and heat at 200 ℃ for 3 hours. The obtained mixture was evaporated at 60℃. During the evaporation process, auxiliary air bubbling was used to promote water evaporation and reduce material loss. Subsequently, the solid product was dried in a vacuum drying oven at 90℃ for 8 h. 0.2 g of the solid product was ground with 0.02 g of nickel foam and evenly spread in a porcelain boat crucible. W = 0.1. In a tube furnace, under nitrogen atmosphere (flow rate 50 mL∙min -1 ), at 2℃ min -1 The temperature was raised to 800°C at a rate of 100 °C. After constant temperature calcination for 1 h at this temperature and atmosphere, 0.07 g of Ni nanoclusters supported by nitrogen and oxygen doped carbon were obtained, with a loading of 11.5%. Transmission electron microscopy images show that Ni is dispersed on nitrogen and oxygen doped carbon in the form of metal nanoclusters ( Figure 5 ). Example 13
[0036] Disperse 5.0 g of melamine resin in 500 mL of water. R = 0.01, transfer the dispersion into a sealed container and heat at 200 ℃ for 3 hours. The obtained mixture was evaporated at 60℃. During the evaporation process, auxiliary air bubbling was used to promote water evaporation and reduce material loss. Subsequently, the solid product was dried in a vacuum drying oven at 90℃ for 8 h. 0.2 g of the solid product and 0.02 g of nickel foam were taken and placed at both ends of a porcelain boat crucible (1.5 cm×4 cm), that is, the solid product was close to the air inlet end and the nickel foam was close to the air outlet end, with a distance of 1 cm between the two. W = 0.1. In a tube furnace, under nitrogen atmosphere (flow rate 50 mL∙min -1 ), at 2℃min -1 The temperature was raised to 800 °C at a rate of 1.5 ℃. After constant temperature calcination for 1 h at this temperature and atmosphere, 0.01 g of nitrogen-oxygen doped carbon-supported single-site Ni catalyst was obtained with a loading of 1.5%. High-angle annular dark field scanning transmission electron microscopy images show that Ni is dispersed on nitrogen-oxygen doped carbon in the form of isolated metal single atom sites ( Figure 6 ).contrast Figure 2 and Figure 6 It can be seen that compared with Example 1, the Ni content is significantly reduced. Embodiment 14
[0037] Disperse 0.5 g of polyethylene terephthalate in 50 mL of acetic acid. R = 0.01. Add 0.005 g of the catalyst of Example 1, C= 0.1%. The mixture was ultrasonically dispersed for 10 min to form a solid-liquid dispersion slurry. The slurry was transferred to a 100 mL microwave reaction tank for microwave-assisted catalytic degradation. The microwave power was 500 W, the reaction temperature was 160 ° C, the reaction pressure was 1.2 MPa, and the reaction time was 20 min. The conversion rate of polyethylene terephthalate was 99%. The degradation products were terephthalic acid and ethylene glycol diacetate, with a terephthalic acid selectivity of 100% and a yield of 99%.
[0038] Comparison examples The comparative example is the same as the process of Example 13, except that the nitrogen-oxygen-doped carbon obtained in the comparative example of Example 1 is used as a catalyst, and the conversion rate of the obtained polyethylene terephthalate is 9.5%. The degradation products are terephthalic acid and ethylene glycol diacetate, the selectivity of terephthalic acid is 100%, and the yield is 9.5%. Embodiment 15
[0039] Disperse 5 g of polyethylene terephthalate in 100 mL of pure water. R = 0.05. Add 0.025 g of the catalyst from Example 2, C = 0.5%. The mixture was ultrasonically dispersed for 5 min to form a solid-liquid dispersion slurry. The slurry was transferred to a microwave reaction tank and heated at 0.5 mL∙min -1 The flow rate was pumped into an engineering plastic reaction coil system with a tube diameter of 1 mm and a length of 10 m, and the degradation reaction was carried out in a microwave high-pressure continuous flow reactor. The reaction was carried out at 170°C and a reaction pressure of 1.4 MPa in a microwave high-pressure reactor under the condition of a microwave power of 1000 W. The residence time of the slurry in the reactor was 15.7 min, and the conversion rate of polyethylene terephthalate was 95%. The degradation products were terephthalic acid and ethylene glycol, with a terephthalic acid selectivity of 100% and a yield of 95%. The time to complete the reaction of 100 mL of slurry was 200 min. The infrared contrast of the terephthalic acid obtained by degradation with the commercial product is as follows: Figure 7 The infrared absorption vibration of the terephthalic acid obtained by degradation is consistent with that of the commercial product. -1 The infrared absorption peak is attributed to the presence of crystal water. This result shows that the purity of the terephthalic acid obtained by degradation is high and close to that of commercial terephthalic acid. Example 16
[0040] Disperse 10 g of polybutylene terephthalate in 20 mL of methanol. R = 0.5. Add 0.1 g of the catalyst of Example 3, C= 1%. The mixture was ultrasonically dispersed for 20 min to form a solid-liquid dispersion slurry. The slurry was transferred to a 100 mL microwave reaction tank for microwave-assisted catalytic degradation. The microwave power was 800 W, the reaction temperature was 150 ° C, the reaction pressure was 2 MPa, and the reaction time was 12.5 min. The conversion rate of polybutylene terephthalate was 98%. The degradation products were dimethyl terephthalate and butanediol, with a selectivity of 100% for dimethyl terephthalate and a yield of 98%. Embodiment 17
[0041] Disperse 5 g of polybutylene terephthalate in 50 mL of acetic acid. R = 0.1. Add 0.125 g of the catalyst of Example 4, C = 2.5%. The mixture was ultrasonically dispersed for 60 min to form a solid-liquid dispersion slurry. The slurry was transferred to a microwave reaction tank and heated at 1 mL∙min -1 The flow rate was pumped into an engineering plastic reaction coil system with a diameter of 1 mm and a length of 10 m, and the degradation reaction was carried out in a microwave high-pressure continuous flow reactor. The reaction was carried out under the conditions of 1800 W microwave power, 190 ° C and 1.6 MPa in the microwave high-pressure reactor. The residence time of the slurry in the reactor was 7.85 min, and the conversion rate of polybutylene terephthalate was 97%. The degradation products were terephthalic acid and butanediol diacetate, with a terephthalic acid selectivity of 99% and a yield of 97%. The time to complete the reaction of 50 mL slurry was 50 min. Embodiment 18
[0042] Disperse 6 g of polycaprolactone in 200 mL of ethanol. R = 0.03. Add 0.24 g of the catalyst of Example 5, C = 4%. The mixture was ultrasonically dispersed for 15 min to form a solid-liquid dispersion slurry. The slurry was transferred to a 500 mL microwave reactor for microwave-assisted catalytic degradation. The microwave power was 1000 W, the reaction temperature was 100 °C, the reaction pressure was 0.8 MPa, and the reaction time was 12 min. The conversion rate of polycaprolactone was 97.5%. The degradation product was ethyl hexanoate with a selectivity of 100% and a yield of 97.5%. Embodiment 19
[0043] Disperse 2 g of polycarbonate in 25 mL of glycerol. R = 0.08. Add 0.016 g of the catalyst of Example 6, C= 0.8%. The mixture was ultrasonically dispersed for 40 min to form a solid-liquid dispersion slurry. The slurry was transferred to a 100 mL microwave reactor for microwave-assisted catalytic degradation. The microwave power was 1600 W, the reaction temperature was 280 °C, the reaction pressure was 0.1 MPa, and the reaction time was 2 min. The conversion rate of polycarbonate was 95.5%. The degradation products were bisphenol A and glycerol carbonate, with a bisphenol A selectivity of 95% and a yield of 91%. Embodiment 20
[0044] 0.15 g of thermosetting epoxy resin powder cured with bisphenol A diglycidyl ether (DER311) and methyl-5-norbornene-2,3-dicarboxylic anhydride was dispersed in 15 mL of pure water. R = 0.01. Add 0.005 g of catalyst from Example 7, C =0.1%. The mixture was ultrasonically dispersed for 10 min to form a solid-liquid dispersion slurry. The slurry was transferred to a 100 mL microwave reaction tank for microwave-assisted catalytic degradation. The microwave power was 500 W, the reaction temperature was 200 °C, the reaction pressure was 1.8 MPa, and the reaction time was 20 min. The conversion rate of thermosetting epoxy resin was 98%. The degradation products were oligomers of bisphenol A and cis-5-norbornene-endo-2,3-dicarboxylic acid, with a yield of 95%. Embodiment 21
[0045] Disperse 4 g of thermoplastic polyurethane soft body polyurethane made of toluene isocyanate and polyethylene glycol in 15 mL of ethylene glycol. R = 0.267. Add 0.008 g of the catalyst of Example 8, C = 0.2%. The mixture was ultrasonically dispersed for 15 min to form a solid-liquid dispersion slurry. The slurry was transferred to a 50 mL microwave reaction tank for microwave-assisted catalytic degradation. The microwave power was 2000 W, the reaction temperature was 280 ° C, the reaction pressure was 0.3 MPa, and the reaction time was 0.5 min. The conversion rate of polyurethane was 97%. The degradation product was polyether polyol with a yield of 89%. Embodiment 22
[0046] 2 g of thermoplastic polyurethane hard polyurethane made of 1, 4-diphenylmethane diisocyanate and butanediol was dispersed in 50 mL of ethylene glycol-water solution (V 乙二醇 :V 水 = 1:1), R = 0.04. Add 0.04 g of the catalyst of Example 9, C= 2%. The mixture was ultrasonically dispersed for 25 min to form a solid-liquid dispersion slurry. The slurry was transferred to a 100 mL microwave reaction tank for microwave-assisted catalytic degradation. The microwave power was 1500 W, the reaction temperature was 180 °C, the reaction pressure was 0.9 MPa, and the reaction time was 1 min. The conversion rate of polyurethane was 100%. The degradation product was polyether polyol with a yield of 84%. Embodiment 23
[0047] 10 g of thermosetting polyurethane prepared from 4,4'-dicyclohexylmethane diisocyanate, 1,2-hexanediol and propylene glycol was dispersed in 100 mL of diethylene glycol solution, R = 0.1. 0.1 g of catalyst from Example 10 was added, C = 1%. The mixture was ultrasonically dispersed for 10 min to form a solid-liquid dispersion slurry. The slurry was transferred to a microwave reaction tank and heated at 2 mL∙min. -1 The flow rate was pumped into an engineering plastic reaction coil system with a diameter of 1 mm and a length of 10 m, and the degradation reaction was carried out in a microwave high-pressure continuous flow reactor. The reaction was carried out under the conditions of 2000 W microwave power, 200 ° C and 0.1 MPa reaction pressure in the microwave high-pressure reactor. The residence time of the slurry in the reactor was 4 min, and the conversion rate of polyurethane was 87%. The degradation product was polyether polyol with a yield of 79%. The time to complete the reaction of 100 mL slurry was 50 min. Embodiment 24
[0048] Disperse 0.5 g of polyethylene terephthalate in 50 mL of acetic acid. R = 0.01. Add 0.005 g of the catalyst of Example 11, C = 0.1%. The mixture was ultrasonically dispersed for 10 min to form a solid-liquid dispersion slurry. The slurry was transferred to a 100 mL microwave reaction tank for microwave-assisted catalytic degradation. The microwave power was 500 W, the reaction temperature was 160 ° C, the reaction pressure was 1.2 MPa, and the reaction time was 20 min. The conversion rate of polyethylene terephthalate was 40%. The degradation products were terephthalic acid and ethylene glycol diacetate, with a terephthalic acid selectivity of 100% and a yield of 20%. Embodiment 25
[0049] Disperse 0.5 g of polyethylene terephthalate in 50 mL of acetic acid. R = 0.01. Add 0.005 g of the catalyst of Example 12, C= 0.1%. The mixture was ultrasonically dispersed for 10 min to form a solid-liquid dispersion slurry. The slurry was transferred to a 100 mL microwave reaction tank for microwave-assisted catalytic degradation. The microwave power was 500 W, the reaction temperature was 160 ° C, the reaction pressure was 1.2 MPa, and the reaction time was 20 min. The conversion rate of polyethylene terephthalate was 55%. The degradation products were terephthalic acid and ethylene glycol diacetate, with a terephthalic acid selectivity of 100% and a yield of 25%. Embodiment 26
[0050] Disperse 0.5 g of polyethylene terephthalate in 50 mL of acetic acid. R = 0.01. Add 0.005 g of the catalyst of Example 13, C = 0.1%. The mixture was ultrasonically dispersed for 10 min to form a solid-liquid dispersion slurry. The slurry was transferred to a 100 mL microwave reaction tank for microwave-assisted catalytic degradation. The microwave power was 500 W, the reaction temperature was 160 ° C, the reaction pressure was 1.2 MPa, and the reaction time was 20 min. The conversion rate of polyethylene terephthalate was 45%. The degradation products were terephthalic acid and ethylene glycol diacetate, the selectivity of terephthalic acid was 100%, and the yield was 45%.
Claims
1. A method for preparing a carbon-doped single-site metal catalyst using nitrogen-containing waste plastics, characterized in that The following steps are involved: (1) Crush the nitrogen-containing waste plastics and disperse them in water, and perform hydrothermal pretreatment at 120-280°C in a closed container; (2) evaporating the solvent and drying to obtain a solid product; (3) The solid product is evenly spread on a heat-resistant substrate, and metal foam is placed on it. The reaction is carried out at 700~1200℃ under an inert atmosphere to obtain a doped carbon-supported single-site metal catalyst.
2. The preparation method according to claim 1, characterized in that: In step (1), the nitrogen-containing waste plastic is selected from melamine resin, melamine urea-formaldehyde resin, urea-formaldehyde resin, and polyurethane.
3. The preparation method according to claim 1, characterized in that: In step (3), the metal foam is selected from foamed iron, foamed nickel, foamed cobalt, foamed copper, foamed silver, foamed nickel-iron or foamed nickel-cobalt.
4. The preparation method according to claim 1, characterized in that: In step (3), the metal loading mass fraction of the obtained carbon-doped supported unit-site metal catalyst is 10-20%.
5. The doped carbon-supported single-site metal catalyst prepared by the method of claim 1.
6. Use of the carbon-doped single-site metal catalyst according to claim 5 in catalytic degradation of polyester, polycarbonate, epoxy resin and polyurethane waste plastics.
7. The use according to claim 6, characterized in that: A catalytic amount of a doped carbon-supported single-site metal catalyst is added to a waste plastic dispersion, and after ultrasonic dispersion, a solid-liquid dispersion slurry is formed, and catalytic degradation is carried out under the assistance of microwaves.
8. The application according to claim 7, characterized in that: The solvent in the waste plastic dispersion is selected from water, methanol, ethanol, acetic acid, ethylene glycol, and diethylene glycol.
9. The use according to claim 7, characterized in that: The microwave power of microwave-assisted catalytic degradation is 500~2000W, the reaction temperature is 100~280℃, and the reaction pressure is 0.1~2 MPa.
10. The use according to claim 7, characterized in that: The polyester plastic is selected from polyethylene terephthalate, polybutylene terephthalate and polycaprolactone.
Citation Information
Patent Citations
Sulfur and nitrogen co-doped carbon-loaded transition metal monatomic catalyst and preparation method thereof
CN117696096A
Preparation method and application of carbon-based monatomic catalyst
CN118054028A
Continuous flow method for macroscopically preparing precious metal monatomic catalyst
CN118079991A
Method for preparing metal monatomic material from melamino-formaldehyde resin, metal monatomic material and application of metal monatomic material
CN111450868A
Method for converting plastic pyrolysis steam into BTX-rich product through microwave catalysis
CN116444332A